Volleyball Game Learning Education Upper Level Elementary School Children - Purwoto, Septyaningrum Putri; Handayani, Heni Yuli; Himawan, Agus; Widodo, Haryo Mukti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2025)
This community service activity aims to provide education about the basics of volleyball to high school students at SDK Maria Fatima, Bangkalan, Madura. Volleyball is one of the sports that is able to develop children's physical, motor, social, and cognitive aspects holistically. However, in the field, various obstacles are still found, such as the lack of understanding of teachers in delivering material effectively, low interest in volleyball sports, and limited basic skills that students have. To answer these problems, this activity is designed through lectures, demonstrations, interactive discussions, and hands-on practice methods with a fun approach and adapted to the characteristics of children's development. The implementation of the activity was carried out for one month and involved 20 upper-class students and teachers at SDK Maria Fatima. The results of the activity showed an increase in students' understanding of basic concepts and techniques of the game of volleyball, an improvement in motor skills in performing basic movements such as passing, serving, and smash, as well as a growth in students' interest and active participation in physical learning activities. In addition, this activity also has a positive impact on teachers in terms of implementing more varied and effective sports learning methods. Thus, this program makes a real contribution to improving the quality of physical education at the elementary school level, especially in volleyball.